Axial pressure impact on pyrolysis behavior of Xinjiang coal: An inspiration for in-situ pyrolysis of tar-rich coal - Bingyang Kou; Qingmin Shi; Shuangming Wang; Qiang Sun; Shidong Cui; Xiaolong Yang; Xinyue Zhao; Junwei Qiao (Fuel Processing Technology)
Tar-rich coal in-situ pyrolysis (TCIP) is a green and low-carbon technology that extracts tar and gas from underground tar-rich coal seams. Overburden pressures are a crucial factor for TCIP that differs from conventional ground pyrolysis. This study investigated the impact of axial pressure on the pyrolysis of Xinjiang tar-rich coal using simulations. The variation of pore structure and volatiles was studied using low-field nuclear magnetic resonance and gas chromatography. Results indicated that pore structure and tar-gas composition evolved synergistically, and presented staged characteristics during pyrolysis under axial stress. 10.0–17.5 MPa, coals compressed to breakage, enhancing pore-fracture connectivity and convective heat transfer during pyrolysis. Pores continued to enlarge, porosity-permeability increased, promoting volatiles release and reducing secondary reactions, leading to increased tar-gas yield, particularly light and phenol oils, CO2, and C2+ gases proportion. Conversely, coals compacted at 20.0–25.0 MPa, pore-fracture connectivity worsened due to fracture closure, decreased convective heat transfer, and weakened pore enlargement phenomenon. The enhancement of matrix heat transfer formed many smaller pyrolysis pores within the coal matrix, but poor connectivity decreased porosity-permeability. This increased the release resistance of volatiles, strengthened secondary reactions, and reduced tar-gas yields. However, the proportion of light and naphthalene oils, CH4, H2, and CO is increasing.